First Study of Bacteremia Caused by Herbaspirillum huttiense in China: A Brief Research Report and Literature Review - Xiangyun Li; Xundi Bao; Guanhua Qiao; Lianzi Wang; Cuixiao Shi; Shuyi Chen; Yuanhong Xu; Meijuan Zheng; Zhongxin Wang (Frontiers in Cellular and Infection Microbiology, 2022)
Bacteremia caused by Herbaspirillum huttiense (H. huttiense) is relatively rare in positive blood cultures. H. huttiense is an opportunistic bacterium in patients with cancer and cirrhosis and has also been described in immunocompromised hosts. In this study, H. huttiense was isolated from a patient with repeated chest tightness and chest pain. Smears were prepared, stained, and examined by microscopy. Single colonies were analyzed by Gram staining, matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS), 16S rRNA sequencing and Next-Generation Sequencing (NGS). Antibiotic sensitivity was assessed by agar dilution. Almost all publications on H. huttiense infections in the PubMed/ScienceDirect/EBSCO databases were reviewed and summarized. Blood sample culturing yielded white, gelatinous, and slightly raised colonies without hemolytic rings. The bacilli were found to be Gram-negative, and MS results showed 99.2% homology with H. huttiense. This was confirmed by 16S rRNA gene sequencing, phylogenetic tree analysis and NGS all of which were homologous with H. huttiense in GenBank. Antibiotic susceptibility tests were performed to determine the minimum inhibitory concentrations (MICs) of imipenem, meropenem, piperacillin-tazobactam, and levofloxacin. A comprehensive literature review revealed that H. huttiense was an emergent pathogen. After medical treatment, the patient’s body temperature returned to normal. This is the first report of bacteremia caused by H. huttiense in China. The findings could improve the awareness and attention of the rare pathogenic microorganisms in China.